PERSEPSI MASYARAKAT TERHADAP PERNIKAHAN DIBAWAH UMUR - Andiansyah; Ernawati , Erna; Fikri , Luthfy Rijalul (Fakultas Ilmu Dakwah dan Komunikasi, 2023)
This research is motivated by the increasing number of underage marriages in the village of Cianangneng, prompting the author to conduct a study on the community's perception of this issue. This research is of a qualitative descriptive nature, and data collection methods include interviews, observations, and documentation. It refers to government regulations (laws) and the provisions of Islamic Sharia law. The research findings indicate that underage marriages still frequently occur in the village of Cinangneng, Tenjolaya Subdistrict, resulting in negative impacts on underage marriage participants, such as a lack of psychological maturity that can affect their lives. Underage marriages are regulated by laws that specify the age or age limits for marriage participants, yet many members of the community still fail to adhere to these government regulations. Underage marriage participants experience both negative and positive impacts. However, the author hopes that this research can change the community's perception of underage marriages, emphasizing that marriage is a continuous act of worship and is expected to bring more benefits than harm.